Structural and fluorescence properties of the 2,2?-methylenediphenoxy and 1,1?-methylenedi-2-naphthoxy cyclotriphosphazene derivatives - Ciftci, Gonul Yenilmez; Eker, Yakup; Senkuytu, Elif; Yüksel, Fatma (Elsevier, 2016)
In the present work, the partially or fully substituted spiro-, ansa, open-chain forms of 2,2'-methylenediphenoxy, 1,1'-methylenedi-2-naphthoxy cyclotriphosphazene derivatives and their spectral properties were reported. The reactions of hexachlorocyclotriphosphazene [trimer, N3P3Cl6, (1)] with 2,2'methylenediphenol (2) and 1,1'-methylenedi-2-naphthol (3) in THF produced new cyclotriphosphazene compounds (4-11). All these compounds (4-11) were fully characterized by elemental analysis, FT-IR, MALDI-TOF mass spectrometry, UV Vis, H-1, C-13 and P-31 NMR spectroscopy. The molecular structures of 4, 5, 7, 9 and 10 were also determined by X-ray crystallography. All five structures were found in monoclinic system, C2ic, P21in or P21/c space groups. The fluorescence behaviour of the studied cyclotriphosphazene derivatives (9-11) were also examined in THF solution. Compound 11 showed the highest fluorescence emission behaviour that of compounds 4-10. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Cyclotriphosphazenes; Trimer; 2,2 '-methylenediphenol; 1,1 '-methylenedi-2-naphthol; P-31 NMR spectroscopy; X-ray crystallography; Fluorescence